2006
DOI: 10.1074/jbc.m604511200
|View full text |Cite
|
Sign up to set email alerts
|

Role of Glutamine Depletion in Directing Tissue-specific Nutrient Stress Responses to L-Asparaginase

Abstract: L-Asparaginase is important in the induction regimen for treating acute lymphoblastic leukemia. Cytotoxic complications are clinically significant problems lacking mechanistic insight. To reveal tissue-specific molecular responses to this drug, mice were administered asparaginase from either Escherichia coli (clinically used) or Wolinella succinogenes (novel, glutaminasefree form). Both enzymes abolished serum asparagine, but only the E. coli form reduced circulating glutamine. E. coli asparaginase reduced pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 65 publications
5
67
0
6
Order By: Relevance
“…Finally, GLUL expression is induced by GCs (Harmon and Thompson, 1982) and we have recently reported that reduced expression of this gene is associated with adverse outcome in B-lineage ALL (Hoffmann et al, 2008). The importance of glutamine in ALL is highlighted by the fact that a significant proportion of the clinical efficacy of L-asparaginase, a cornerstone of therapy for this disease, is actually due to the glutaminase activity contained within such preparations (Reinert et al, 2006). The current data suggest that changes to amino-acid metabolism are not only fundamental to the leukemic phenotype but may also contribute to GC resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, GLUL expression is induced by GCs (Harmon and Thompson, 1982) and we have recently reported that reduced expression of this gene is associated with adverse outcome in B-lineage ALL (Hoffmann et al, 2008). The importance of glutamine in ALL is highlighted by the fact that a significant proportion of the clinical efficacy of L-asparaginase, a cornerstone of therapy for this disease, is actually due to the glutaminase activity contained within such preparations (Reinert et al, 2006). The current data suggest that changes to amino-acid metabolism are not only fundamental to the leukemic phenotype but may also contribute to GC resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Not PERK-Previously, we showed that treatment with asparaginase activates p-eIF2 in liver and spleen but not pancreas (4). In that study, a slight increase in p-eIF2 was detectable in the liver of GCN2 Ϫ/Ϫ mice 1-6 h after asparaginase injection.…”
Section: Phosphorylation Of Eif2 By Asparaginase Requires Gcn2 Andmentioning
confidence: 71%
“…Measurement of L-Asparaginase Activity-The activity of experimental L-asparaginase derived from E. coli (Elspar product from Merck) was determined by the Nesslerization technique, as described previously (4,19). Briefly, the production of ammonia by L-asparaginase over time was expressed relative to the slope of known ammonia standards.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Disturbances in hemostasis due to amino-acid depletion are probably a local effect, that is, in the liver only. 53,54 Outcome and prognostic factors Both the clinical response to PEG-asparaginase window and the in vitro sensitivity to L-asparaginase are predictive for outcome. The prognostic relevance of the in vitro sensitivity has been previously shown.…”
Section: Clinical Toxicity Allergic Reactions and Changes In Hemostasismentioning
confidence: 99%